Komposisi Mikroorganisme Pada fermentasi Umbi Ubi Kayu Pahit Menjadi â€œWikau Maomboâ€ - Nurhayani H., Muhiddin (bionature, 2011)
The aim of the research was to know total count of microorganisms and character of group of type mikroorganisme which natural grow of during fermentation process of " Wikau Maombo". This research was conducted in Biological Laboratory of Faculty of Mathematics and Natural Sciences of University Haluoleo. The research use is experimental method having the character of explorate. The total count of microorganisms calculated with the method of " Standard of Plate Count", and characterize of group of type of microorganisms by spread plate isolation method use the medium Nutrient Agar for the bacteria, Potato Dextrose Agar for the mould , and Yeast Malt Agar for the yeast. The calculation and isolation of microorganisms conducted every day during 4 day fermentation, with the fresh bitter cassava root control before fermentation. The result of research show total count of bacteria of fresh cassava root equal to 1,1 x 106 CFU/mL and at "Wikau Maomboâ€ after fermentation, respectively 1, 2, 3 and 4 day become 7,5 x 106 CFU/ mL, 4,3 x 107 CFU/mL, 0,9 x 107 CFU/mL, and 3,0 x 107 CFU/mL, by 20 kinds of isolate group. The total count of mould of fresh cassava root equal to 1,1 x 105 CFU/mL, and respectively at "Wikau Maombo" after fermentation, that is equal to 1,0 x 107 CFU/mL, 2,1 x 107 CFU/mL, 1,7Â  x 107 CFU/mL, and 1,6 x 107 CFU/mL. the Isolates of mould consisted by four kinds of isolate group.The total count of yeast of cassava rootÂ  ofÂ  before fermentation of equal to 0,9 x 106 CFU/mL, and at â€œwikau maombo" after fermentation, respectively, that are 3,9 x 106 CFU/mL, 2,8 x 106 CFU/ml, 2,0 x 106 CFU/mL, and 0,8 x 106 CFU/mL. The solates of yeast consisted by four kinds of isolate group.